1989
DOI: 10.1002/pssa.2211150229
|View full text |Cite
|
Sign up to set email alerts
|

Far IR spectra of ferroelectric Rochelle Salt and sodium ammonium tartrate

Abstract: There are only a few studies on the FIR transmission of tartrates. However, they lead to interesting problems related to surface layers, phase transitions, and soft mode. New results will precise these views on Rochelle Salt and also give the FIR spectra of sodium‐ammonium tartrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Early far-infrared (FIR) measurements [25] on Rochelle salt showed that a thin film has higher transmission than a thick film, and that extra peaks appear in thin films. Recent FIR measurements [26] on PbTiO 3 and PZT film have been carried out, but there was no discussion of size or surface effects.…”
Section: Introductionmentioning
confidence: 99%
“…Early far-infrared (FIR) measurements [25] on Rochelle salt showed that a thin film has higher transmission than a thick film, and that extra peaks appear in thin films. Recent FIR measurements [26] on PbTiO 3 and PZT film have been carried out, but there was no discussion of size or surface effects.…”
Section: Introductionmentioning
confidence: 99%